LEARNING BY DOING: SPANISH APPLIED LINGUISTICS AS A LIVING LAB - Pérez, Grisel M. GarcÃa (European Scientific Journal, ESJ, 2015)
This paper addresses the impact of a sustainable teaching model in the Faculty of Creative and Critical Studies at the University of British Columbia in the Okanagan (UBCO). During the past few years, the growing number of students wanting to learn Spanish has become evident, class size has increased from 30 to 70, but manpower has remained the same. The trade of has been that it has become almost impossible to give immediate individual feedback to the students in the classroom, so monitoring language learning has been affected. In language learning, feedback is understood as any communication between the instructor and the student that provides information about the student’s performance in a given task. When this communication breaks, the learning process is affected. So, this eminent class increase promoted the idea of creating a learning space for students taking a course in Spanish Applied Linguistics. Most specifically, the course was designed to engage undergraduate fourth year students in project based learning to foster the integration of teaching and research. Theoretical applied linguistic concepts were introduced in class, and the experiential learning approach was used to allow the students opportunities outside the classroom to enact the concepts learned through classroom observations, tutoring, service learning, creation of supplementary materials and on-going reflection. The paper includes a detailed description on how the course was conducted, what learning opportunities the students were exposed to, and what the overall results of the course were.